Backstepping Glycemic Control of Type 1 Diabetes for Implementation on an Embedded System - Mounir Djouima; Said Drid; Driss Mehdi (International Journal Bioautomation, 2018)
In this paper a nonlinear control intended for Blood glucose regulation for Type 1 Diabetes patients is considered. The control law is designed using the Lyapunov theory associated with a Kalman filter to estimate the system states. The asymptotic stability of the overall system is theoretically proven. The proposed control scheme will be implemented in a low cost embedded system. The simulation results confirm the effectiveness of the proposed control.